TERIMA-2: National Extension of Thrombolytic Treatment with Recombinant Streptokinase in Acute Myocardial Infarct in Cuba - The TERIMA Group of Investigators; Marrero-Miragaya, María Acelia (Thrombosis and Haemostasis, 2000)
Aim: The extension of recombinant streptokinase (rSK) use in Cuba and to evaluate its effect on in-hospital mortality of patients with acute myocardial infarct (AMI). Methods: A phase IV clinical study was performed in 52 hospitals from the 14 Cuban provinces. Patients (any age) with ST segment elevation or bundle branch block were included if they came less than 12 h after the onset of AMI symptoms, without contraindications for thrombolytic therapy. They received 1.5 × 106 IU of rSK (Heberkinasa, Heberbiotec, Havana) intravenously, during one hour. Endpoints were death due to cardiac (pump failure, wall rupture, arrhythmia) or any cause and cardiovascular events at hospital release. Results: The study included 2923 patients, 22 – 98 years-old, 74.4% men, which represented 37.2% of the total AMI patients attended at the participating hospitals from November 1992 to May 1995. Aspirin was given to 92.5% and betablockers to 65.3%. AMI was confirmed in 93.5% of the patients. The mean symptoms – rSK infusion time interval was 5.25 h (22.3% of the patients treated within the first 3 h). 302 patients died, 80.1% of them due to cardiac causes, 12 attributed to rSK treatment, and 16 to non-cardiac causes. This 10.4% mortality represents a 4% absolute and a 28.3% relative reduction (179 lives saved per year) as compared to a survey made before rSK treatment was introduced. In a logistic regression analysis, mortality was favored by age, symptoms – infusion time, Killip class, and not having taken aspirin or betablockers. Feminine gender was close to the limit of significance. The more frequent adverse events were arrhythmias and hypotension during infusion. Major bleeding occurred in 27 patients (9 strokes). Conclusion: Local recombinant-DNA biotechnology can influence on a major health problem with favorable cost/ and risk/ benefit balances, not possible in a developing country with an imported drug. The further extension of this treatment in the country is feasible and recommended, monitored through an appropriate pharmacosurveillance program.
Keywords: Streptokinase; thrombolysis; acute myocardial infarction